(untitled) (American Journal of Business Management, Economics and Banking, 2026)
This article examines modern prospects for financing the material and technical base of higher education institutions through a comparative analysis of official international datasets, national policy documents, and peer-reviewed literature. The study focuses on how systems fund laboratories, digital infrastructure, capital facilities, and research platforms. Evidence indicates that sustainable financing requires a blended structure combining core public funding, weighted allocation formulas, targeted capital grants, competitive project finance, moderate performance-based funding, and carefully governed revenue diversification. Cross-regional comparison demonstrates that public-dominant systems retain stronger baseline infrastructure security, while mixed public-private systems achieve higher spending but face volatility risks. Uzbekistan’s PF-58 reform package is examined as a significant example of explicit infrastructure-linked financing. The article concludes that the material and technical base should be financed through a portfolio model based on adequacy, transparency, full-cost logic, and lifecycle asset management.